Zjawiska paraspołeczne – teoria, przegląd badań i perspektywy - Reszka, Dominika (Kultura-Społeczeństwo-Edukacja, 2024)
The purpose of this article is to present the issue of parasocial phenomena. For this purpose, the concept of Horton and Wohl, which initiated research on parasocial phenomena, is presented in detail. The results of previous research on parasocial phenomena are cited. On their basis, it was indicated which people can take on the role of a media figure in parasocial phenomena. Features that attract viewers to a media figure are also listed. The role of transmission-related factors on the development of parasocial phenomena was also discussed. Criticism of the theory of parasocial phenomena regarding the theoretical concept and the research conducted was also indicated. The current direction of research on parasocial phenomena was also discussed, along with an indication of potential perspectives.